Silicon Carbide n-IGBTs: Structure Optimization for Ruggedness Enhancement - Almpanis, Ioannis; Antoniou, Marina; Evans, Paul; Empringham, Lee; Gammon, Peter; Undrea, Florin; Mawby, Philip; Lophitis, Neophytos (My University, 2024)
In recent years, silicon carbide (SiC) based devices are increasingly replacing their silicon counterparts in power conversion applications due to their performance superiority. SiC insulated-gate bipolar transistors are particularly interesting as they appear to be the most appropriate for medium and high voltage applications due to their low on-state voltage drop for devices rated at 10kV or higher. However, the widespread adoption of SiC IGBT requires rugged devices capable of surviving in harsh conditions. By using Sentaurus TCAD and validated models based on published experimental results, the short-circuit, unintentional turn-on and dV/dt ruggedness of SiC IGBTs are comprehensively explored and the impact of device parameters on the overall IGBT ruggedness were identified. This paper aims to propose the most efficient methods for IGBT ruggedness enhancement on the device level.
Keywords: dV/dt; insulated-gate bipolar transistor (IGBT); ruggedness; short circuit; silicon carbide (SiC); TCAD simulation; unintentional turn-on